(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Fibroblast growth factor 23 (FGF-23) and its cofactor alfa klotho, are one of the most important factors, directly and indirectly, involved in the process of calcification and atherosclerosis. This study aimed to evaluate the efficacy of a combination of regular exercise during dialysis on quality of life and markers including FGF-23, alfa klotho, and fetuin-A levels. Methods. Forty-five hemodialysis patients aged 61 ± 9.02 years and weight 69 ± 11.25 kg were randomly divided into two training, EX (n = 24) and control groups, CON (n = 21). The EX group patients participated in a 16-week combined aerobic and resistance exercise program during dialysis. Bone markers including, FGF-23, klotho, fetuin-A, were measured before and at the end of the study in both groups. Statistical analysis for comparing data change during study by SPSS software and the P value was set at .05. Results. In the control group in the secondary assessment, reduction in quality of life was observed (P < .05). Significant change in growth factor 23, CRP, and fetuin-A was not observed in exercise and control groups (P > .05), however significant rising of klotho was observed in treated patients (P < .05). Also, combined training reduced the amount of phosphorus, parathyroid hormone; significantly (P < .05). Conclusion. This study showed that regular exercise during dialysis improves quality of life and physical functions. No significant change in FGF-23 and CRP were observed during the study. However significant rising of klotho and reduction of iPTH and phosphorous levels were observed in treated patients.